Ion-Induced Synthesis of Alginate Fibroid Hydrogel for Heavy Metal Ions Removal - Kong, Chuncai; Zhao, Xueqi; Li, Yingju; Yang, Sen; Chen, Yong Mei; Yang, Zhimao (Frontiers in Chemistry, 2020)
Design and synthesis of environmentally friendly adsorbents with high adsorption capacities are urgently needed to control pollution of water resources. In this work, a calcium ion-induced approach was used to synthesize sodium alginate fibroid hydrogel (AFH). The as-prepared AFH has certain mechanical strength, and the mechanical strength is enhanced especially after the adsorption of heavy metal ions, which is very convenient for the recovery. AFH exhibited excellent adsorption performances for Cu2+, Cd2+ and Pb2+ ions and displayed very high saturated adsorption capacities (Qe) of 315.92 mg·g-1 (Cu2+), 232.35 mg·g-1 (Cd2+) and 465.22 mg·g-1 (Pb2+) with optimized pH values (3.0-4.0) and temperature (303 K). The study of isotherms and kinetics indicated that adsorption processes of heavy metal ions fitted well with the pseudo-second-order kinetics model and the Langmuir model. Pb2+ was found to have the strongest competitiveness among the three heavy metal ions. Thus, AFH has great application prospects in the field of heavy metal ions removing from wastewater.